(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
Organizational and managerial activity consists of a certain set of relatively constant tasks that require solutions in the face of change and uncertainty, that is, competencies are formed by the environment. This article reveals the concept of "organizational and managerial abilities" for undergraduates in socio-cultural activities, also analyzes the organizational and managerial skills that are part of professional competence.